2009
DOI: 10.1097/eja.0b013e328329b0c6
|View full text |Cite
|
Sign up to set email alerts
|

‘Scheduled’ dosing of lornoxicam provides analgesia superior to that provided by ‘on request’ dosing following craniotomy

Abstract: 'Scheduled' analgesia with lornoxicam was more effective for treating post-craniotomy pain than 'on request' analgesia with lornoxicam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…[ 92 ] Studies provide inconclusive evidence for the safety of drugs such as ketorolac,[ 76 ] demonstrating a higher risk for intracranial hematoma associated with intraoperative use but not in the postoperative setting. [ 59 ] Further, trial studies do not show an increase in complication rates for hematomas, renal failure, or peptic ulcers[ 28 ] following neurosurgery. Though their use remains controversial, emerging studies are now focusing on selective COX-2 inhibitors that appear to be safer with regard to coagulation effects.…”
Section: Introductionmentioning
confidence: 99%
“…[ 92 ] Studies provide inconclusive evidence for the safety of drugs such as ketorolac,[ 76 ] demonstrating a higher risk for intracranial hematoma associated with intraoperative use but not in the postoperative setting. [ 59 ] Further, trial studies do not show an increase in complication rates for hematomas, renal failure, or peptic ulcers[ 28 ] following neurosurgery. Though their use remains controversial, emerging studies are now focusing on selective COX-2 inhibitors that appear to be safer with regard to coagulation effects.…”
Section: Introductionmentioning
confidence: 99%
“…A structured review on time-scheduled opioid dosing for post-operative pain management [12] concluded that there is “sparse empirical work warranting endorsement of this dosing regimen.” Subsequently, several trials of time-scheduled opioid dosing reported benefits relative to pain-contingent dosing in postoperative pain management [6,7,11,19]. Whether findings for time-scheduled opioid dosing in post-operative pain management translate to COT in ambulatory care settings has not been examined.…”
mentioning
confidence: 99%
“…Numerous studies showed that a time-scheduled pattern was better than a pain-contingent pattern (PRN) in postoperative pain management. The former with adequate dosing could provide stable therapeutic blood levels and a continuous relieving effect for acute pain [12, 45, 47, 55, 59]. Our time-scheduled analgesic was consistent with this principle and its efficacy was observed by better functional end points.…”
Section: Discussionmentioning
confidence: 61%